DEVELOPMENT OF SMALL BUSINESS AND ENTREPRENEURSHIP - A SPRINGBOARD FOR ENSURING MACROECONOMIC STABILITY - Sobirovna, Kosimova Dilorom; Gafurovich, Akbarov Nodir; Abdugafarovich, Sobirov Abdurasul; Hamrakulovich, Kochimov Abdujamil (The journal of contemporary issues in business and government, 2021)
Creation of normative and legal instruments to stimulate the growth and development of small business and private entrepreneurship, state support in solving daily cross-cutting issues, attraction of public and foreign investments (assets and capital) in this sector under government guarantees, advanced know-how of small firms and enterprises Acceleration and coordination by the state of innovative cooperation with Howe centers is crucial for the stabilization of macroeconomic indicators. The directions proposed in the article are focused on the prospects for improving and developing the state of small business and private entrepreneurship, which is an important attribute of ensuring the welfare and macroeconomic stability of a large part of the population due to its ability to increase efficiency and profitability.